Communication Dynamics of Tourism Awareness Groups in Developing Community-Based Edu-Tourism: An IMOI Perspective in Village Government - Bhakti, Aditya Aditya Dwi Putra; Prakoso, Havidz Ageng; Wibowo, Novin; Nasvian, Moch. Fuad; Ningsih, Gumoyo Mumpuni; Flores, Reymund Botin (Journal of Local Government Issues, 2025)
This study investigates the communication dynamics of Tourism Awareness Groups (Pokdarwis) in developing community-based educational tourism within the framework of village development policy. While current policy directions emphasize sustainable and participatory tourism, local communities often face structural limitations in mobilizing resources and institutional support. To address this issue, a qualitative exploratory case study was conducted in Sumbertangkil Village, East Java. Data were gathered through semi-structured interviews, focus group discussions, and participant observation, and then analyzed using the Input–Mediator–Output–Input (IMOI) model. The findings demonstrate that prosocial bonds, emotional cohesion, and charismatic leadership provide strong intrinsic motivation and short-term momentum for edu-tourism initiatives. Members have begun to reinterpret local practices, such as coffee farming and storytelling, as valuable educational assets. However, organizational weaknesses persist, including role ambiguity, the absence of systematic documentation, and reliance on informal communication channels. These deficiencies prevent outputs from being reintegrated into new inputs, thereby inhibiting the formation of a continuous learning cycle. Theoretically, this research extends the IMOI framework by applying it to a rural community-based tourism context, showing how strong social capital interacts with weak institutional structures. Practically, the study highlights the importance of strengthening internal communication systems, formalizing participatory leadership, and adopting simple digital tools to improve documentation and evaluation. For policymakers and practitioners, the results underscore the need to integrate Pokdarwis into village planning mechanisms and provide facilitative support to enhance their organizational capacity. Strengthening these aspects will enable Pokdarwis to function as learning organizations capable of sustaining educational tourism programs over time.